Complex congenital heart and lung defects as a cause of hydrops fetalis in French bulldogs –micro-CT with contrast study - Olga Szaluś-Jordanow; Karolina Barszcz; Wojciech Mądry; Michał Buczyński; Michał Czopowicz; Adam Gierulski; Agata Moroz-Fik; Zofia Nowek; Marcin Mickiewicz; Michał Grzegorczyk; Jakub Jaroszewicz; Sylwia Tarka; et al. (Scientific Reports)
Abstract Limited data are available on the causes of hydrops fetalis in dogs. Congenital heart defects may be an important contributing factor. Standard autopsy often fails to provide a comprehensive and accurate diagnosis on very small hearts. This study was carried out on five French bulldog puppies all presenting with advanced hydrops fetalis and four diagnosed with pulmonary hypoplasia at autopsy. The body weight of the dogs ranged from 142 to 687 g and the heart with lungs weighed from 4.5 to 23.6 g. The hearts and pulmonary vessels were filled with barium contrast, and micro-CT scans of the physiologically connected heart and lungs were performed. In all five puppies, we confirmed congenital heart defects including: Puppy #1. Perimembranous ventricular septal defect and aortic dextroposition; Puppy #2. Interrupted aortic arch with aortic valve dysplasia and aortic stenosis; Puppy #3. Tricuspid valve dysplasia and bicuspid pulmonary trunk valve; Puppy #4. Aortic stenosis and ventricular septal defect; Puppy #5. Tricuspid valve dysplasia. Additionally, four puppies had pulmonary vascular hypoplasia. Contrast-enhanced micro-CT can provide highly accurate diagnosis of complex congenital heart and lung defects. Examination of the heart in conjunction with the lungs appears to be a rational approach in animals with hydrops fetalis.